2014
DOI: 10.1680/macr.13.00310
|View full text |Cite
|
Sign up to set email alerts
|

A new empirical model for shear strength of reinforced concrete beam–column connections

Abstract: A new empirical model to estimate the joint shear strength of both exterior and interior beam-column connections is proposed. In the model, four parameters that have the most influence on joint shear strength are considered.Among these four, a new parameter is introduced to consider the bond condition and the possibility of beam bars transferring joint shear force into the columns. Consideration of this parameter in the model significantly improves the accuracy of the predicted joint shear strength. To calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…From their study, the concrete compressive strength f c , in-plane geometry (interior, exterior, or knee connections), dimensions of the beams and columns (h b , b b , h c , b c ), joint transversal reinforcement, and beam reinforcement are among the influencing parameters for the shear strength of the conventional beam-column joint. Furthermore, the bonding condition which is strongly influenced by the development length and the details of the beam reinforcement bars, are also known as the influencing parameters for the shear strength of the conventional joint [4]. In the following part, the influencing parameters for the joint shear strength of connections with headed bars are evaluated by using the collected database.…”
Section: Influencing Parameters Of Beam-column Joint Using Headed Barsmentioning
confidence: 99%
See 3 more Smart Citations
“…From their study, the concrete compressive strength f c , in-plane geometry (interior, exterior, or knee connections), dimensions of the beams and columns (h b , b b , h c , b c ), joint transversal reinforcement, and beam reinforcement are among the influencing parameters for the shear strength of the conventional beam-column joint. Furthermore, the bonding condition which is strongly influenced by the development length and the details of the beam reinforcement bars, are also known as the influencing parameters for the shear strength of the conventional joint [4]. In the following part, the influencing parameters for the joint shear strength of connections with headed bars are evaluated by using the collected database.…”
Section: Influencing Parameters Of Beam-column Joint Using Headed Barsmentioning
confidence: 99%
“…This design strategy is called the "strong column-weak beam" philosophy. In practice, the prediction of the beam bending moment capacity is relatively relevant, while the prediction of the joint shear strength is still to be investigated [1][2][3][4][5]. This is why numerous studies have been performed to investigate the behavior of beam-column joints.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many experimental studies have shown that failure of the joint not only occurred at the joint core, but also developed into the upper and lower columns Tran, 2014, 2015;Wang et al, 2012). In addition, a recent study (Tran et al, 2014) showed that the contacting area between the beam longitudinal reinforcement and the surrounding concrete has a significant role in the joint shear strength. These facts lead to the idea that the beam longitudinal reinforcement tensile force transferred just a fraction of that force into the joint core.…”
Section: Introductionmentioning
confidence: 99%